Using the Tuning Methodology to design the founding benchmark competences for a new academic professional field: the case of Advanced Rehabilitation Technologies - Ann-Marie Hughes; Chris Freeman; Tom Banks; Hans Savelberg; Mary Gobbi (Universidad de Deusto, 2016)
Designing innovative high quality educational programmes to meet the workforce needs in emerging interdisciplinary areas of practice can present challenges to academics, students, employers and industrial partners. This paper demonstrates how the Tuning Process successfully helped to construct benchmark learning outcomes and competences in the area of healthcare practice where advanced technologies are used to improve movement namely Rehabilitation Technologies (RTs). The paper also discusses the engagement of patients, carers and carer organisations within the development of competences.  Due to changing demographics, limited resources and the availability of technology, rehabilitation technologies are starting to be used for the assessment and treatment of patients. However there are currently no European transnational Bachelor or Master programmes targeted at educating people for the design, development, use and evaluation of these technologies. The contemporary field is predominantly staffed and resourced by engineering scientists and clinicians who were primarily educated in their primary discipline. The first generations of rehabilitation technologists have established this specialist field through invention, perseverance, and collaborative working. However, there is now a recognition that new and complementary skill sets are required by future graduates, whether engineering scientists or clinicians, so as to better meet the needs of clients and the employment market whether in the domains of industry, research, academia or clinical practice.  This project demonstrates how a group of European specialist rehabilitation technologists, supported by educationalists, collaborated to identify and develop the core competences and learning outcomes required by future Master's (second cycle) graduates in this new discipline. Building on the work of the Tuning Process and applying the principles embedded in the Bologna Process, future employability needs are determined through an imaginative, technological and cost conscious entrepreneurial approach to education. Published online: 01 June 2016